Polymorphism in polymers: A tool to tailor material's properties. Issue 2 (3rd February 2020) - De Rosa, Claudio; Scoti, Miriam; Di Girolamo, Rocco; de Ballesteros, Odda Ruiz; Auriemma, Finizia; Malafronte, Anna
Abstract: In this review, the phenomenon of polymorphism in polymers is discussed on the basis of the thermodynamic stability of different polymorphs that defines the conformations of chains in the crystalline lattice and the packing mode. In particular, we show that the symmetry and energy stability of the chain conformation, the crystal density and entropy of packing, and the presence of defects and disorder in the crystals are the main factors that define the mode of crystallization of polymers and induce polymorphism. How specific polymorphs are selected and the effects of the molecular structure and processing conditions on polymorphism are analyzed. How crystallization of particular polymorphs affects the material's properties and ultimate applications is also discussed. The polymorphic behaviors of isotactic polypropylene and poly(1‐butene) are described as examples of how processing and the controlled modification of the molecular structure of polyolefins using methods of controlled synthesis that allow controlled incorporation of configurational and constitutional defects may drive crystallization of a desired polymorph. The possibility to select a particular polymorph using these strategies results in a tool to tailor the physical and mechanical properties of polymers. Abstract : Polymorphism in polymers affects the material's properties and ultimate applications. Specific polymorphs can be selected using various strategies. The controlled modification of the molecular structure of polyolefins using methods of controlled synthesis that allow controlled incorporation of constitutional and/or configurational defects, may drive crystallization of a desired polymorph resulting in a tool to tailor the physical and mechanical properties of polymers.